Development of Web-Based Lecturer Achievement Index Information System to Improve Assessment Accuracy: Pengembangan Sistem Informasi Indeks Prestasi Dosen Berbasis Web untuk Meningkatkan Akurasi Penilaian - Gemilang, Michael Surya; Anita; Zulkarnain, Adnan (Procedia of Social Sciences and Humanities, 2022)
The lecturer achievement index is a benchmark for assessing the quality of teaching staff or lecturers. The process of improving the quality of lecturers should be planned and realized in line with needs, so that in the end it can achieve the vision and mission that has been set. The calculation of the lecturer's achievement index is done by collecting tridharma data (teaching, research and community service). At the STIKI Malang, the tridharma data collection process was obtained from various work units via email. In addition, the existing process has been carried out manually by the secretary of the study program. This results in the recording process taking a long time and the potential for recap errors is greater. So we need a lecturer achievement index system that can help related work units in processing lecturer achievement index data. With the creation of this system, it is hoped that it can accelerate and facilitate STIKI Malang to process lecturer achievement index data and increase accuracy in calculating the lecturer achievement index value.